Resistance of the African blue tick (Rhipicephalus (Boophilus) decoloratus) to Macrocyclic Lactones in the Eastern Cape, South Africa - Lesenyeho, Setjhaba Kenneth (University of the Free State, 2019)
Macrocyclic Lactones (MLs) are anti-parasitic drugs used to control blue ticks, mites and endoparasites. Resistance development of the Asiatic blue tick (Rhipicephalus (Boophilus) microplus) to Ivermectin (IVM) (product of MLs) was reported in Brazil, Uruguay, Mexico and Australia due to the frequent and misuse of this product. There has not been any incidents of tick populations resistant to MLs treatment that were reported up to now in South Africa for the Asiatic blue tick or African blue tick (Rhipicephalus (Boophilus) decoloratus) species although an increase in the use of MLs for tick control was also inevitable. However, pharmaceutical company agents are receiving a rising number of complaints from Eastern Cape producers concerning inadequate control of blue ticks by MLs. Therefore, a methodology had to be established to confirm MLs resistance of South African blue tick strains. This entailed comparing two Shaw Larval Immersion Tests (SLIT), the test-tube and pie-plate SLIT, determining a suitable diluent, TritonX/Ethanol vs. twice-distilled water and a post-exposure timeframe for mortality determination after 24, 48 and 72 hours, to detect resistance and prevent tick death from sources other than the exposure to the chemical. It was determined that the pie-plate SLIT was the most suitable methodology to determine MLs resistance as it was more efficient, less time consuming and caused less mechanical death to the tick larvae than the test-tube SLIT. Twice-distilled water and evaluation of mortality 24 hours post-exposure, were the most suitable diluent and post-exposure time, respectively, for the pie-plate SLIT. Reference strains, of both blue tick species, not previously exposed to MLs were obtained from ClinVet International. These reference strains were used to determine lethal concentrations (LC 50 and LC99) by means of Probit (Polo Suite) analysis. The reference strains of both blue tick species were found to be more susceptible to MLs than blue ticks in Brazil, Australia and Mexico. Blue ticks collected from farms in the Eastern Cape were divided into two groups, ticks that were previously exposed to MLs in the past five years, and those that have not been exposed to MLs in the last five years. The LCs and Confidence Intervals 95% (CI95%) of the field strains were calculated to determine the Factor of Resistance (FR) and resistance levels according to an established range. Strains not exposed to IVM in the past five years were confirmed to be susceptible to IVM, while strains suspected of being resistant to IVM due to complaints of poor to moderate results after treating with IVM also fitted into these ranges to be classified as resistant. More research on these ranges is needed in South Africa to determine when a classification of emerging resistance is valid and when a population can be classified as resistant as this range could not accommodate all the strains. More extensive sampling over different periods and comparing different generations will also be needed to confirm resistance on some of the farms.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2019
Keywords: Macrocylic lactones; Ivermectin; Rhipicephalus (Boophilus) decoloratus; Rhipicephalus (Boophilus) microplus; Eastern Cape; Shaw Larval Immersion Test